A Case of Secondary Syphilis with the Extragenital Chancre on the Nipple. (11th February 2020) - Wang, Xiao Yan; Juliandri,; Liu, Zi Jing; Zhang, Jia Wen; Liu, Yun Yi; Wang, Da-Guang; Xu, Yang
Abstract : Syphilis is a sexually transmitted disease caused by Treponema pallidum . The signs and symptoms of syphilis vary depending on which of the four stages it presents. The primary stage of syphilis classically presents with a painless ulcer (chancre). We report a case of the extragenital chancre on the nipple which is examined from skin biopsy and immunohistochemistry. This case showed that it is important to identify the special site's pruritus erythema by pathology and serological examination.